2005
DOI: 10.1103/physrevb.71.035306
|View full text |Cite
|
Sign up to set email alerts
|

Transistor behavior via Au clusters etched from electrodes in an acidic gating solution: Metal nanoparticles mimicking conducting polymers

Abstract: 14853* These authors contributed equally to this work.We report that the electrical conductance between closely-spaced gold electrodes in acid solution can be turned from off [insulating; I] to on [conducting; C] to off again by monotonically sweeping a gate voltage applied to the solution. We propose that this ICI transistor action is due to an electrochemical process dependent on nanoparticles etched from the surface of the gold electrodes. These measurements mimic closely the characteristics of nanoscale ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Recently, it has been demonstrated that large bias voltages applied to Au surfaces can induce electrochemical processes that lead to formation of Au nanoparticles of diameter on the order of a few nanometer, [10,11] and these nanoparticles self-assemble into a granular structure. [11] In the prior work, [9] we showed that the electron localization length in the nanojunction is finite at low temperatures. To summarize, samples with resistance larger than approximately R Q displayed Coulomb blockade.…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that large bias voltages applied to Au surfaces can induce electrochemical processes that lead to formation of Au nanoparticles of diameter on the order of a few nanometer, [10,11] and these nanoparticles self-assemble into a granular structure. [11] In the prior work, [9] we showed that the electron localization length in the nanojunction is finite at low temperatures. To summarize, samples with resistance larger than approximately R Q displayed Coulomb blockade.…”
mentioning
confidence: 99%
“…Granular disorder has been recently confirmed in Au samples created by electro-chemistry. [11,12] It has been shown that large electric fields near Au surfaces induce formation of Au nanoparticles of diameter of few nanometers, which assemble into a granular structure. [12] Theoretically, granular metals are similar to Fermi-Liquids.…”
Section: Granular Nano-bridge Modelmentioning
confidence: 99%
“…Recently, granular disorder has been directly observed in Au-nanoelectrodes grown by electrochemistry. [11,12] In particular, an electrochemical growth process at certain gate voltages created a granular material consisting of Au clusters with oxidized surface. Granular disorder can cause characteristics that resemble single-electron transistors, and researchers were cautioned about interpreting transistor effects in molecular-electronics experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 42 In that review, and in the studies mentioned above, NP formation triggered by an oxidation route has not been mentioned at all, which is electrochemically more common. 43 45 …”
Section: Introductionmentioning
confidence: 99%